Complementary Approaches to Imaging Subcellular Lipid Architectures in Live Bacteria Using Phosphorescent Iridium Complexes and Raman Spectroscopy. Issue 45 (11th July 2019) - Ranieri, Anna Maria; Caporale, Chiara; Fiorini, Valentina; Hubbard, Alysia; Rigby, Paul; Stagni, Stefano; Watkin, Elizabeth; Ogden, Mark I.; Hackett, Mark J.; Massi, Massimiliano
Abstract: A family of three neutral iridium(III) tetrazolato complexes are investigated as bacterial imaging agents. The complexes offer a facile tuning of the emission colour from green (520 nm) to red (600 nm) in aqueous media, while keeping the excitation wavelength unchanged. The three complexes do not inhibit the bacterial growth of Bacillus Cereus, used as a model in this study, and exhibit extremely fast cellular uptake. After a minute incubation time, the nontoxic complexes show subcellular localisation in spherical structures identified as lipid vacuoles. Confocal Raman imaging has been exploited for the first time on live bacteria, to provide direct and label‐free mapping of the lipid‐enriched organelles within B. cereus, complementing the use of luminescent probes. Examination of the Raman spectra not only confirmed the presence of lipophilic inclusions in B. cereus but offered additional information about their chemical composition, suggesting that the lipid vacuoles may contain polyhydroxybutyrate (PHB). Abstract : Iridium(III) tetrazolato complexes are investigated as bacterial imaging agents, representing the first example of metal‐based probe staining lipids in bacteria. Complementing the use of these luminescent probes, confocal Raman imaging has been exploited for the first time on live bacteria, providing direct mapping and chemical characterisation of these lipid vacuoles (see scheme).